Analysis of the structural integrity of a frozen wall during a mine shaft excavation using temperature monitoring data (Fracture and Structural Integrity, 2022)
This paper describes the results of the temperature monitoring of a frozen wall (FW) around the skip shaft of a potash mine under construction. The data on temperature measurements in control-thermal boreholes were used to parameterize the mathematical model of heat transfer, which allowed for the reconstruction of the temperature field throughout the entire cooled and frozen soil volume. The resulting temperature distribution in the FW zone for greater than 1 year was used to determine the distribution of the strength properties and calculate the temporary change in the limiting value of the external lateral load on an FW of a given thickness and specified thermomechanical properties. The obtained dependencies of the maximum external load on the FW can be used to optimize the operation mode of the freezing station at the ice holding stage (or passive freezing) to increase the energy efficiency of the system and ensure the structural integrity of the FW.
Keywords: Frozen wall; Artificial ground freezing; Mine shaft; Temperature monitoring; Structural integrity; Optimization of freezing parameters